The Effect of Financial Accounting Practices and Management Accounting Practices on MSME’s Economic sustainability - Yobi Nagoya Pratiwi; Febrianty; Poppy Febrina; Mutiara Lusiana Annisa (Politeknik Ganesha Medan, 2022)
This study aims to find empirical evidence regarding the level of adoption of financial accounting practices, assessment of accounting practices to MSMEs, and to see the correlation between financial accounting practices and management accounting practices of MSMEs in Palembang. Total of 1,103 MSMEs registered at Cooperatives and Micro, Small and Medium Enterprises Office is the research population. The sampling technique used the Taro Yamane formula to determine the size of the sample. After obtaining the number of samples, the random sampling method was used to select the MSMEs that were used as research samples. The precision of the sample used in this study was 0.2 and the research sample obtained was 50 samples. The data analysis method used was descriptive statistics and simple and multiple linear regression with a significance level of 0.05. The result is that there is a significant positive effect between financial accounting practices and management accounting on economic sustainability with a probability of 0.006 < 0.005. The most widely adopted financial accounting practice is the recording of sales and purchase transactions, while the most widely used management accounting practice is in operational budget planning.